National Dogmatism or the Logic of Consociation : Text is published in periodical "Survey" 1-2, 2006 - Ibrulj, Nijaz (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
The text examines the contemporary social and political ontology of Bosnia and Herzegovina as a basis for understanding the social and historic prerequisites of the accession of Bosnia and Herzegovina to the European Union. The basic tenet is that the status functions of the social ontology in Bosnia and Herzegovina lack a rationally acceptable structure because they produce contradictory institutional objects, facts, processes and states of affairs, while the status functions of political ontology fail to produce deontic values / rights because they create separate intentional contents and a contradictory attitude to them. These contradictions are connected to a hyper-national attitude and lead to nationalism. The tenet is argued through the confrontation of the contents of three dogmas of nationalism and three conditions for a normal consociation of the nations in Bosnia and Herzegovina. The text suggests that Bosnia and Herzegovina does not havea paradigm for a rigid-ideological, militaristic or religious state communityin EU member states, rather a paradigm for consociation of nations and a state of free citizens who, through their social and political ontology, need to collectively accept common deontic capabilities / rights, which the European Union also accepts through its status functions.